Downhill Running Excessive Training Inhibits Hypertrophy in Mice Skeletal Muscles with Different Fiber Type Composition. Issue 5 (29th September 2015) - da Rocha, Alisson L.; Pereira, Bruno C.; Pauli, José R.; de Souza, Claudio T.; Teixeira, Giovana R.; Lira, Fábio S.; Cintra, Dennys E.; Ropelle, Eduardo R.; Júnior, Carlos R.B.; da Silva, Adelino S.R.
Abstract : The aim of this study was to verify the effects of running overtraining protocols performed in downhill, uphill, and without inclination on the proteins related to hypertrophy signaling pathway in extensor digitorum longus (EDL) and soleus of C57BL/6 mice. We also performed histological and stereological analyses. Rodents were divided into control (CT; sedentary mice), overtrained by downhill running (OTR/down), overtrained by uphill running (OTR/up), and overtrained by running without inclination (OTR). The incremental load, exhaustive, and grip force tests were used as performance evaluation parameters. 36 h after the grip force test, EDL and soleus were removed and immediately used for immunoblotting analysis or stored at −80°C for histological and stereological analyses. For EDL, OTR/down decreased the protein kinase B (Akt) and tuberous sclerosis protein 2 (TSC2) phosphorylation (p), and increased myostatin, receptor‐activated Smads (pSMAD2‐3), and insulin receptor substrate‐1 (pIRS‐1; Ser307/636). OTR/down also presented low and high relative proportions of cytoplasm and connective tissue, respectively. OTR/up increased the mammalian target of rapamycin (pmTOR), 70‐kDa ribosomal protein S6 kinase 1 (pS6K1) and pSMAD2‐3, and decreased pTSC2. OTR decreased pTSC2 and increased pIRS‐1 (Ser636). For soleus, OTR/down increased S6 ribosomal protein (pS6RP) and pSMAD2‐3, and decreased pIRS‐1 (Ser639). OTR/up decreased pS6K1, pS6RP and pIRS‐1 (Ser639), and increased pTSC2 (Ser939), and pSMAD2‐3. OTR increased pS6RP, 4E‐binding protein‐1 (p4E‐BP1), pTSC2 (Ser939), and pSMAD2‐3, and decreased pIRS‐1 (Ser639). In summary, OTR/down inhibited the skeletal muscle hypertrophy with concomitant signs of atrophy in EDL. The effects of OTR/up and OTR depended on the analyzed skeletal muscle type. J. Cell. Physiol. 231: 1045–1056, 2016. © 2015 Wiley Periodicals, Inc.